STRUCTURAL, SEMANTIC, AND LINGUO-CULTURAL FEATURES OF ANTHROPONYMS IN ENGLISH AND UZBEK (International journal of artificial intelligence, 2025)
Anthroponyms, or personal names, serve as significant linguistic units that reflect cultural, historical, and social characteristics of a given society. This study explores the structural, semantic, and linguo-cultural features of anthroponyms in English and Uzbek. By analyzing the formation, meaning, and cultural influences of personal names in these languages, we identify key similarities and differences.